Poverty and mental health in post-war countries: The case of Uganda and Sierra Leone - Jotteranda, Fabrice; Shour, Abdul R.; Anguzu, Ronald (Academic Press., 2020)
The impact of environmental factors on brain development in children and adolescents has become a growing research focus in recent years. Low socioeconomic status (SES) has been linked to adverse health outcomes, mental disorders, and low academic achievements. Research on the impact of adverse events on brain development, however, has mostly focused on first-world countries like the United States or countries in the Western world. The aim of this chapter is twofold: (1) to investigate particular mental health needs and challenges in the aftermath of civil unrest, political violence and continuous economic and political difficulties in Uganda and Sierra Leone; and (2) to examine how neuroethics can help develop strategies to address the mental health crisis that has not been adequately assessed and addressed in Uganda and Sierra Leone. In particular, this chapter addresses the question of how to improve access to new neuroscientific knowledge and treatment options relevant to the impact of poverty and violence.
Keywords: Mental disorders; Neuroscience of poverty; War; Mental health; Poverty